ANALISIS PRAKTIK KEPERAWATAN DENGAN INTERVENSI PEMBERIAN NASI BASMATI DINGIN DENGAN METODE PIRING PADA PASIEN DIABETES MELITUS TIPE 2 DI WILAYAH PUSKESMAS LOK BAHU SAMARINDA - Kadir, Abd; Widiastuti, Hesti Prawita; Mountia, Ariesta; Fitri, Ulia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Background: Based on IDF data, the number of Diabetes Mellitus sufferers in the world in 2025 is estimated to reach 589 million, aged 20–79 years. An unbalanced diet can worsen blood glucose control and reduce insulin sensitivity. To control glucose levels, a Diabetes Mellitus diet is required. Objective: to analyze the intervention of providing cold basmati rice with the plate method to reduce blood glucose levels in Type 2 Diabetes Mellitus patients. Method: The study used a descriptive case study method. The intervention was carried out by providing basmati rice cooked at 100°C for 30–40 minutes, then cooled for 6–12 hours at room temperature. Results: The intervention of providing cold basmati rice with the plate method showed a decrease in GDS levels, case 1 post-intervention GDS value on the first day was 227 mg/dl, the second day was 213 mg/dl, the third day was 204 mg/dl, an average value of 134 mg/dl (normal). In case 2, there was an average GDS value of -40 mg/dl, categorized as hypoglycemia, the GDS value of the first day of intervention was 209 mg/dl, the second day was 168 mg/dl, the third day was 204 mg/dl. Case 3, the evaluation results showed a significant decrease, the first day was 296 mg/dl, the second day was 183 mg/dl, and the third day was 88 mg/dl, an average value of 195 mg/dl was obtained, categorized as hyperglycemia. Conclusion: Providing cold basmati rice with the plate method has been shown to reduce blood glucose levels.Keywords: Cold Rice Basmati, Diabetes Mellitus Type 2, Public Health Center, The Plates